2020
DOI: 10.3390/ijms21041196
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Nuclear and Mitochondrial DNA, Expression of Mitochondria-Related Genes in Different Brain Regions in Rats after Whole-Body X-ray Irradiation

Abstract: Studies of molecular changes occurred in various brain regions after whole-body irradiation showed a significant increase in terms of the importance in gaining insight into how to slow down or prevent the development of long-term side effects such as carcinogenesis, cognitive impairment and other pathologies. We have analyzed nDNA damage and repair, changes in mitochondrial DNA (mtDNA) copy number and in the level of mtDNA heteroplasmy, and also examined changes in the expression of genes involved in the regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…The possible underlying mechanism resulting in loss-of-function of the above sodium channel and potassium channels may be related to the production of reactive oxygen species (ROS) upon irradiation. We did not measure ROS formation in the present study; however, it is well known that ROS is accumulated in cells after high-dose irradiation [ 22 , 23 , 24 ]. Furthermore, the recovery pattern after radiation-induced rapid change herein observed is identical to that of mitochondrial ROS production and recovery [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The possible underlying mechanism resulting in loss-of-function of the above sodium channel and potassium channels may be related to the production of reactive oxygen species (ROS) upon irradiation. We did not measure ROS formation in the present study; however, it is well known that ROS is accumulated in cells after high-dose irradiation [ 22 , 23 , 24 ]. Furthermore, the recovery pattern after radiation-induced rapid change herein observed is identical to that of mitochondrial ROS production and recovery [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…All these molecules are involved in the regulation of oxidative phosphorylation. Mitochondrial genes are maternally inherited, and the majority (99%) of mitochondrial proteins are regulated by nuclear DNA (nDNA), translated in the cytoplasm and then transported to the mitochondrial compartment [ 19 ]. Mitochondria are being replaced within 10-25 days, and old mitochondria are replaced by autophagy (mitophagy).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was shown that after irradiation of the rat head with X-rays, DSBs nDNA in the cortical neurons persisted for a long post-radiation time [ 46 ]. We also recently reported that DNA damage repair in irradiated rats is slower in cortical tissue than in hippocampal tissue [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…To determine the damage and repair of nDNA and mtDNA, we used the long amplicon quantitative polymerase chain reaction (LA-QPCR) method [ 17 ] taking into account our previous experience [ 18 ]. In these analyses, we used (2U/μL) KAPA Long Range Hot Start Kit (KAPA Biosystems, Humboldt County, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation